Sexting Motivation Scale (EMS) in Peruvian Youth - Joel Palomino-Ccasa; Analí Tuanama Shupingahua; Lady Pamela Torrejon Chuqui; Jhon Kenedy Saldaña Sánchez; María Yndrid Tantaruna Diaz; Segundo Salatiel Malca-Peralta; Dany Yudet Millones-Liza (Sexes)
The sharing of explicit sexual images through virtual platforms has grown exponentially in recent generations, causing various issues such as low self-esteem, sextortion, and cyberbullying, among others. Therefore, it is imperative to have a deeper understanding of this issue. This research aims to construct an instrument that allows for the identification of the motivations that lead to the practice of sexting in young university students. The research had two phases: conducting an Exploratory Factor Analysis, which included 320 university students (48.2% female and 51.8% male) aged between 18 and 30 (M = 20.4; SD = 2.62). In the second phase, 1056 university students (55.9% female and 44.1% male) within the same age range as the first phase participated (M = 22.38; SD = 2.64), for whom a Confirmatory Factor Analysis (CFA) was conducted. The final version of the scale consisted of a unidimensional model comprising eight items that assess internal and external motivations leading to the practice of sexting, with an adequate fit index (CFI = 0.991, TLI = 0.988, and RMSEA = 0.068). Additionally, an omega coefficient of 0.93 was found, indicating adequate reliability. It was concluded that the Sexting Motivation Scale (EMS by its initials in Spanish) demonstrates good reliability and construct validity, making it suitable for measuring motivation for sexting.